Menyoal Pemilihan Umum Serentak Dan Penegakan Hukumnya - Sugita, I Made (Jayapangus Press, 2025)
Through MK decision no. 14/PUU-XI/2013 concerning the review of Law no. 42 of 2008 concerning the General Election of the President and Vice President states that general elections in Indonesia are held simultaneously between the legislature and the executive, which is generally known as simultaneous general elections. However, in its implementation, this simultaneous general election still experienced a number of problems. This is why law enforcement in simultaneous general elections is very important to realize honest and democratic elections. The aim of this research is to examine the problems that occurred in simultaneous elections and their law enforcement. The research method used in this research is normative legal research, which refers to doctrine and theory as well as statutory regulations and previous research that are relevant to the problem at hand. The research results show that several problems that arise related to simultaneous general elections include general election logistics issues, updating the final voter list, errors in vote counting due to damaged or invalid ballot papers, as well as money politics problems that still occur. General election law enforcement must pay attention to three benchmarks, namely General Election Administration Provisions (KAP), General Election Criminal Provisions (KPP), and General Election Ethics Provisions (KEEP). These three elements need to be empowered and regulated repeatedly in order to create law enforcement and democratic resolution of election disputes.